2017
DOI: 10.3354/meps12316
|View full text |Cite
|
Sign up to set email alerts
|

Geography and life history traits account for the accumulation of cryptic diversity among Indo-West Pacific coral reef fishes

Abstract: Indo-West Pacific coral reef fishes form speciose ecological communities. A biogeographically meaningful interpretation of diversity patterns in this region requires accurate inventories of species. Previous studies have suggested that biogeographic scenarios for Indo-West Pacific coral reef fishes are compromised by an unacknowledged yet substantial amount of cryptic diversity. DNA barcoding, the use of a mitochondrial gene as an internal species tag for species identification, has opened new perspectives on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 91 publications
8
22
1
Order By: Relevance
“…The ratio reported here, for instance, is twice as high as the value reported for the well-known North American fauna (April, Mayden, Hanner & Bernatchez L, 2011). This ratio may be expected to decrease, however, when expanding the spatial coverage of the present study outside of the YR as it has been previously reported for the North American and European ichthyofaunas (April, Mayden, Hanner & Bernatchez L, 2011;Geiger, 2002;Hubert et al, 2008a;Knebelsberger et al 2015 small sized species with short generation times, a biological characteristic that has been suggested to enhance the accumulation of divergence among diversifying species (April, Hanner, Mayden, & Bernatchez, 2013;Hubert, Dettai, & Pruvost, 2018). Along the same line, these 7 species are characteristic of flowing portions of the main streams and tributaries in hilly areas of the watersheds (Chen, 1998).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The ratio reported here, for instance, is twice as high as the value reported for the well-known North American fauna (April, Mayden, Hanner & Bernatchez L, 2011). This ratio may be expected to decrease, however, when expanding the spatial coverage of the present study outside of the YR as it has been previously reported for the North American and European ichthyofaunas (April, Mayden, Hanner & Bernatchez L, 2011;Geiger, 2002;Hubert et al, 2008a;Knebelsberger et al 2015 small sized species with short generation times, a biological characteristic that has been suggested to enhance the accumulation of divergence among diversifying species (April, Hanner, Mayden, & Bernatchez, 2013;Hubert, Dettai, & Pruvost, 2018). Along the same line, these 7 species are characteristic of flowing portions of the main streams and tributaries in hilly areas of the watersheds (Chen, 1998).…”
Section: Discussionsupporting
confidence: 53%
“…Multiple OTUs confined to a single species were detected among 7 species including Acheilognathus macropterus (three OTUs), Channa asiatica (two OTUs), Distoechodon tumirostris (two OTUs), Hemibagrus macropterus (three OTUs), Hemibarbus maculatus (three OTUs), Liobagrus marginatoides (two OTUs) and Sinogastromyzon szechuanensis (two OTUs). Most of these species with multiple and private OTUs are small sized species with short generation times, a biological characteristic that has been suggested to enhance the accumulation of divergence among diversifying species (April, Hanner, Mayden, & Bernatchez, ; Hubert, Dettai, & Pruvost, ). Along the same line, these 7 species are characteristic of flowing portions of the main streams and tributaries in hilly areas of the watersheds (Chen, ).…”
Section: Discussionmentioning
confidence: 99%
“…The three T. maxima mitochondrial lineages from the WIO and the Red Sea belonged to a well‐supported clade, which diverged from a distinct clade occurring in the north‐western Pacific Ocean (Su et al, ) and in the Coral Triangle, (‘clade 3’ of Keyse et al, ). This genetic divergence was caused by the emergence of the Mid‐Indian Ocean Barrier (MIOB) and the Indo‐Pacific Barrier (IPB), whose roles in shaping the genetic make‐up of a large number of species have been widely discussed (Borsa et al, ; Bowen et al, ; Carpenter et al, ; Gaither & Rocha, ; Hodge & Bellwood, ; Hubert et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The average genetic distances between individuals within species, genera, and families were 0.24%, 11.16%, and 19.01%, respectively, in general agreement with previous reports of marine fishes. For example, the average genetic distances of Australian fishes within species, genera, and families were 0.39%, 9.93%, and 15.46%, respectively ( Ward et al, 2005 ); intra-species distance of South Africa and Australia fishes were 0.21% and 0.28%, respectively ( Zemlak et al, 2009 ); Indian marine fishes were 0.30% (conspecifics), 6.60% (congenerics) and 9.91% (confamilial) ( Lakra et al, 2011 ); divergence of Indo-Pacific coral reef fishes was 1.06% ( Hubert et al, 2012 ); South China Sea fishes divergence were 0.32%, 17.26% and 20.10% within species, genera, and families, respectively ( Wang et al, 2012 ); mean intergeneric distance of fishes from the Caribbean and western central Atlantic regions was 16.6% ( Weigt et al, 2012 ); within-species genetic distances of Indo-West Pacific coral reef fishes was 1.12% ( Hubert et al, 2017 ); genetic distances of fishes from Rongchey Bay, China were 0.21% (conspecifics), 5.28% (congenerics), and 21.30% (confamilial) ( Wang et al, 2018 ); and shore fishes in French Polynesia were 0.66% within species and 12.28% within genera ( Delrieu-Trottin et al, 2019 ). These conspecific genetic distances of less than 2% are in agreement with the species delimitation threshold as proposed by Ward (2009) which further supports the monophyly of each presumed species in this study.…”
Section: Discussionmentioning
confidence: 99%